Research on the Reform of Talent Training Mode for the Light Chemical Engineering under the Background of New Engineering - Xugang DANG; Xuechuan WANG; Xinhua LIU; Huijie ZHANG (Pige Kexue Yu Gongcheng, 2024)
In order to actively respond to industrial change and the new round of scientific and technological revolution, China's higher engineering education put forward the construction of “new engineering”, which points out the direction for the reform of university education. Shaanxi University of Science and Technology, light chemical engineering should give full play to the characteristics of disciplines and specialties as well as the advantages of talent cultivation, and further build a talent cultivation mode to meet the requirements of the construction of new engineering disciplines, so as to cultivate high-quality talents for the domestic light industry.